Opportunities for the Cardiovascular Community in the Precision Medicine Initiative. Issue 2 (12th January 2016) - Shah, Svati H.; Arnett, Donna; Houser, Steven R.; Ginsburg, Geoffrey S.; MacRae, Calum; Mital, Seema; Loscalzo, Joseph; Hall, Jennifer L.
Abstract : The Precision Medicine Initiative recently announced by President Barack Obama seeks to move the field of precision medicine more rapidly into clinical care. Precision medicine revolves around the concept of integrating individual-level data including genomics, biomarkers, lifestyle and other environmental factors, wearable device physiological data, and information from electronic health records to ultimately provide better clinical care to individual patients. The Precision Medicine Initiative as currently structured will primarily fund efforts in cancer genomics with longer-term goals of advancing precision medicine to all areas of health, and will be supported through creation of a 1 million person cohort study across the United States. This focused effort on precision medicine provides scientists, clinicians, and patients within the cardiovascular community an opportunity to work together boldly to advance clinical care; the community needs to be aware and engaged in the process as it progresses. This article provides a framework for potential involvement of the cardiovascular community in the Precision Medicine Initiative, while highlighting significant challenges for its successful implementation.